Implementing a Reproducible Foot and Vaccine Clinic Model to Address Healthcare Needs of People Experiencing Homelessness - Wuebbolt, Caitlin; Andres, Sarah; Chen , Ricki; Pullano, Theresa; Gilligan, Alexandra; Dzik, Alyssa; Christie, Emilie; Chowdhury, Allison; Milling, David (Journal of Student-Run Clinics, 2024)
Background: Homeless Health, Education, Awareness and Leadership in Street Medicine (HEALS) is a nonprofit, medical student-run organization. The mission of HEALS is to address the medical and psychosocial needs of people experiencing homelessness (PEH). Through street medicine outreach initiatives, HEALS works to improve health outcomes associated with unstable housing and limited access to healthcare. The HEALS Foot and Vaccine Clinic was developed to screen for and treat vascular insufficiency, chronic and acute wounds, and foot-related pathologies, and provide vaccinations to prevent infectious illnesses. This clinic also aimed to prevent exposure-related injuries by providing proper footwear and direct access to care. Aim: Our objective is to create a reproducible foot and vaccine clinic model for student-run clinics to address the needs of PEH through interprofessional collaboration and service learning. Methods: The event was funded through a crowdfunding campaign and donations and was hosted at a local shelter. Medical students and physicians employed by the medical school partnered with five community outreach programs to provide medical care. The Department of Health (DoH) administered vaccinations against common viral diseases. Results: Through crowdfunding campaigns, 6,646.00 was raised to contribute to the cost of boots, hygiene kits for attendees, and cleaning supplies, budgeted at 5,198.00. Forty-seven individuals experiencing homelessness were provided with foot care and twenty-six vaccines were administered. The DoH administered twelve hepatitis A, five coronavirus disease 2019 (COVID-19), and nine influenza vaccinations at this event. Successive members of HEALS have since replicated this model to replicate foot and vaccine clinics and expand outreach to the neighboring county, yielding increased event attendance and funding. Using this model, student-run free clinics may implement similar initiatives within their own communities to address the complex needs of PEH.